The Washington manual rheumatology subspecialty consult - González-Mayda, María C.; Ranganathan, Prabha (Washington manual subspecialty consult series., 2021)
"As we started to plan for the fourth edition of this manual, it became clear that there have been tremendous advances in rheumatology, especially in new treatments, in the last eight years"--